Future directions for the concept of salutogenesis: a position article. (20th June 2019) - Bauer, G F; Roy, M; Bakibinga, P; Contu, P; Downe, S; Eriksson, M; Espnes, G A; Jensen, B B; Juvinya Canal, D; Lindström, B; Mana, A; Mittelmark, M B; et al.
Abstract: Aaron Antonovsky advanced the concept of salutogenesis almost four decades ago (Antonovsky, Health, Stress and Coping . Jossey-Bass, San Francisco, CA, 1979; Unravelling the Mystery of Health . Jossey-Bass, San Francisco, CA, 1987). Salutogenesis posits that life experiences shape the sense of coherence (SOC) that helps to mobilize resources to cope with stressors and manage tension successfully (determining one's movement on the health Ease/Dis-ease continuum). Antonovsky considered the three-dimensional SOC (i.e. comprehensibility, manageability, meaningfulness) as the key answer to his question about the origin of health. The field of health promotion has adopted the concept of salutogenesis as reflected in the international Handbook of Salutogenesis (Mittelmark et al., The Handbook of Salutogenesis. Springer, New York, 2016). However, health promotion mostly builds on the more vague, general salutogenic orientation that implies the need to foster resources and capacities to promote health and wellbeing. To strengthen the knowledge base of salutogenesis, the Global Working Group on Salutogenesis (GWG-Sal) of the International Union of Health Promotion and Education produced the Handbook of Salutogenesis . During the creation of the handbook and the regular meetings of the GWG-Sal, the working group identified four key conceptual issues to be advanced: (i) the overall salutogenic model of health; (ii) the SOC concept; (iii) the design of salutogenic interventions and change processes in complex systems; (iv) the application of salutogenesis beyond health sector. For each of these areas, we first highlight Antonovsky's original contribution and then present suggestions for future development. These ideas will help guide GWG-Sal's work to strengthen salutogenesis as a theory base for health promotion.